Canonical WNT signaling pathway in oral squamous cell carcinoma prognosis (Research, Society and Development, 2022)
The aim of the study was to demonstrate the immunohistochemical expression of the wnt/b-catenin pathway in oral carcinoma cells (OSCC), through a literature review. For this, a search was performed in the PubMed and SciELO databases with the keywords “β-catenin”, “oral squamous cell carcinoma”, “OSCC” and “Wnt signaling” with the Boolean AND operator. The inclusion criteria adopted were articles published in English, in vitro, in situ articles or clinical trials from 2010 to 2021 that relate the canonical WNT signaling pathway with oral squamous cell carcinoma and the exclusion criteria considered were duplicate articles, literature review and that did not address the issue. After reading the title, abstract, and full content of each of the studies, 110 articles were selected. IncRNA compounds, enzymes, hexachlorophene derivatives and lignin isolated from Taiwania were able to suppress growth and metastasis by inhibiting the WNT/β-catenin pathway. Cancer stem cells, PON2 type enzymes, nicotine intake, cytokine TNF-α and FAD1 gene are able to increase growth and metastasis by inhibiting the same pathway. Therefore, the expression of these biomarkers can influence the prognosis of cancer cells and help practitioners to explore new possible therapeutic effects in OSSC by modulating the Wnt/β-catenin pathway.